POTENSI WISATA ALAM AIR TERJUN EFRATA DI KABUPATEN SAMOSIR - Donargo, Sepdwiyana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The purpose of this study was to identify the natural tourism potential of Efrata Waterfall in Samosir Regency. Reviewing the accessibility conditions, supporting infrastructure, and obstacles faced in its development as a tourist destination. The research method used is descriptive qualitative with data collection techniques through field observations, interviews with local communities, and documentation studies. The results of the study indicate that Efrata Waterfall has a high tourist attraction in the form of natural beauty that is still pristine, fast flowing water, and surrounding scenery that supports nature recreation activities such as trekking and photography. In terms of accessibility, the location can be reached by public and private vehicles, but the road conditions to the location are still inadequate. The facilities available are still limited, such as toilets, small shops, and simple places of worship. The obstacles faced are limited infrastructure, minimal promotion, lack of local community involvement, and the absence of integrated management. There needs to be an improvement in facilities and infrastructure, digital promotion strategies, and empowerment of local communities in managing the Efrata waterfall nature tourism in Samosir Regency.